A Review over Mitochondrial Diseases Due to mtDNA Mutations: Recent Advances and Remedial Aspects - Bharadwaj, Alok (Infectious Disorders - Drug Targets, 2025)
Mitochondria, also called ‘powerhouse of the cell’, is meant for energy generation in eukaryotic cells. This action is performed by mitochondria through the oxidative phosphorylation (OXPHOS) of the respiratory chain (RC). Based on the functioning of the cell, the number of mitochondria varies up to thousands in number. Mutations in the mitochondrial DNA (mtDNA) and/or nuclear DNA (nDNA) genes may lead to the generation of primary mitochondrial disease (PMD) that affects the structure and function of mitochondria. The diagnosis of such mitochondrial diseases occurs in early childhood and it can lead to serious, fetal and multi-organ diseases. Understanding epigenetic events and changes in the pathway can help improve the effectiveness of treatment. However, there are several reasons lack of the disease symptoms (age, sign, symptoms, morbidity and lethality), restricted availability of preclinical models along with extensive phenotypes that hamper the development of efficient drugs. Despite the introduction of new treatments and the encouraging results of treatments and therapies, there is no effective cure for PMD.This article contains information about the changes associated with cytopathic diseases that make possible the analysis of various diseases by genetic techniques. Increasing our understanding of how mitochondrial DNA mutations affect mitochondrial metabolism and subsequently result in neurodegenerative disease will prove vital to the development of targeted therapies and treatments.
Keywords: genetic techniques